Mechanism of Pyrogallol Red Oxidation Induced by Free Radicals and Reactive Oxidant Species. a Kinetic and Spectroelectrochemistry Study - Ureta-Zanartu, M; Lissi-Gervaso, E; Aspee-Lamas, A (American Chemical Society, 2013)
Pyrogallol red (PGR) presents high reactivity toward reactive (radical and nonradical) species (RS). This property of PGR, together with its characteristic spectroscopic absorption in the visible region, has allowed developing methodologies aimed at evaluating the antioxidant capacity of foods, beverages, and human fluids. These methods are based on the evaluation of the consumption of PGR induced by RS and its inhibition by antioxidants. However, at present, there are no reports regarding the degradation mechanism of PGR, limiting the extrapolation to how antioxidants behave in different systems comprising different RS. In the present study, we evaluate the kinetics of PGR consumption promoted by different RS (peroxyl radicals, peroxynitrite, nitrogen dioxide, and hypochlorite) using spectroscopic techniques and detection of product by HPLC mass spectrometry. The same pattern of oxidation and spectroscopic properties of the products is observed, independently of the RS employed. Mass analysis indicates the formation of only one product identified as a quinone derivative, excluding the formation of peroxides or hydroperoxides and/or chlorinated compounds, in agreement with FOX s assays and oxygen consumption experiments. Cyclic voltammetry, carried out at different pH s, shows an irreversible oxidation of PGR, indicating the initial formation of a phenoxy radical and a second charge transfer reaction generating an ortho-quinone derivative. Spectroelectrochemical oxidation of PGR shows oxidation products with identical UV-visible absorption properties to those observed in RS-induced oxidation. © 2013 American Chemical Society.